A Theoretical Study on the Role of Digital Marketing Management in Increasing MSME Sales: A Literature Review - Aisha Nurrahma Naifa; Zahra Jannatul Firdausi; Mashudi (Managing: Jurnal Bisnis dan Manajemen, 2026)
This research aims to theoretically examine the role of digital marketing management in increasing sales of Micro, Small and Medium Enterprises (MSMEs). This research begins with very rapid developments in information and communication technology that have revolutionized the way businesses operate throughout the world, including in the MSME sector. Digital transformation requires business actors to adapt to new ways of marketing products and building relationships with consumers. The main emphasis in this research is to analyze how digital marketing strategies can be utilized optimally by MSME players to increase market access and optimize competitive position. The method used is a descriptive qualitative approach through literature study, through collection and analysis of various sources of relevant information. The research results show that digital marketing management has an important role in helping the development of MSMEs, especially related to the efficiency of spending on promotions, relationships with customers, and increasing product exposure in cyberspace. These findings confirm that adapting to digital technology is a strategic step for MSMEs to survive and advance in the digital economy era.